Excavating to Excess? Implications of the Last Decade of Archaeology in Israel - Kletter, Raz; De-Groot, Alon (Journal of Mediterranean Archaeology, 2001)
For the first time, there exists a database about all archaeological fieldwork carried out in the state of Israel during the last decade. Documenting a total of 2200 excavation projects (excluding surveys), it shows that the numbers of all types of projects are constantly and sharply rising: the 153 excavations in 1989 more than doubled in 1998 to 333. Yet final publications lag far behind-an illogical situation, if archaeology is reckoned to be a scientific activity. A related problem, not yet discussed in Israel, is that archaeological sites are not an endless resource, and for too long we have been treating ancient sites as did American bison-hunters in the nineteenth century. Thus a radical measure is needed: to stop unnecessary excavations. While it is impossible to halt salvage excavations, a moratorium on new licenses for a few years is feasible. Only if we can restrain our burning desire to excavate so much will we be able to divert funds towards earlier projects, and their publication.